Definitions of experience from the review of the currents of phenomenology and pragmatism - Peña Baeza, Alonso (MAD, 2024)
This paper examines the notion of experience from the perspectives of phenomenology and pragmatism, two philosophical currents that, although distinct, both emphasize the importance of experience. On the one hand, phenomenology focuses on the structure of consciousness and subjective experience. On the other hand, pragmatism focuses on utility and action. Despite these fundamental differences, both approaches view experience as crucial. Phenomenology explores the perception of the world, while pragmatism highlights the connection between experience and action. The integration of these perspectives can be complex, but it is possible with careful analysis. Various authors reveal complex philosophical influences, fusing phenomenological and pragmatic elements from the notion of experience. Varela highlights experience as the foundation of knowledge, integrating naturalistic pragmatic approaches. Van Manen finds similarities between lived experience and aspects of both phenomenology and pragmatism. Rorty focuses on the consequences of experience in the subjective representation of the world without notable tensions. Finally, it is suggested that phenomenology and pragmatism, despite their differences, can complement each other in the study of experience, providing a richer and more multifaceted understanding of it.